An Investigation of Pre-Service Primary School Teachers' Narrative Text Writing Skills for Four Operations Problems - Eser, Rabia Sena Akbaba; Kubanç, Yasemin (Erzurum Kültür Eğitim Vakfı, 2023)
The aim of this study is to examine the narrative text writing skills of prospective primary school teachers for four operations problems. The data of the study were collected according to the document analysis technique, one of the qualitative research methods, and descriptive analysis method was used to analyze the data. The participants of the study consisted of 30 pre-service teachers studying in the Department of Classroom Teaching at a state university. A total of 30 narrative texts written by 3rd grade students were evaluated according to the "Narrative text evaluation form for four operations problems" developed by the researchers, which has four main headings (form, language and expression, narrative text elements and problem situation). As a result of the research, it was concluded that pre-service teachers. It was concluded that the pre-service primary school teachers, who partially mastered the dimensions of the narrative text, were deficient in issues such as elaboration, spelling and punctuation, could not use the elements of the narrative text at a sufficient level and needed to improve these skills. With regard to the problem situation, it is seen that the given information in the texts written by the pre-service teachers, who are generally familiar with the outcomes for the four operations, are mostly clearly expressed, except for the texts written for multiplication.

Bu araştırmanın amacı sınıf öğretmeni adaylarının dört işlem problemlerine yönelik öyküleyici metin yazma becerilerini incelemektir. Araştırmanın verileri, nitel araştırma yöntemlerinden doküman incelemesi tekniğine göre toplanmıştır ve verilerin analiz edilmesinde betimsel analiz yöntemi kullanılmıştır. Araştırmanın katılımcılarını bir devlet üniversitesinde Sınıf Öğretmenliği bölümünde öğrenim gören 30 öğretmen adayı oluşturmaktadır. 3.sınıf öğrencilerine yazdırılan toplam 30 öyküleyici metin, araştırmacılar tarafından geliştirilen ve dört ana başlığa (biçim, dil ve anlatım, öyküleyici metin unsurları ve problem durumu) sahip “Dört işlem problemlerine yönelik öyküleyici metin değerlendirme formu”na göre değerlendirilmiştir. Araştırma sonucunda öğretmen adaylarının sonucuna ulaşılmıştır. Öyküleyici metnin boyutlarına kısmen hâkim olan sınıf öğretmeni adaylarının ayrıntılandırma, yazım-noktalama gibi hususlarda eksik olduğu, öyküleyici metin unsurlarını yeterli düzeyde kullanamadıkları ve bu becerilerini geliştirmeleri gerektiği sonucuna ulaşılmıştır. Problem durumuna ilişkin de dört işleme yönelik kazanımlara genel olarak vakıf olan öğretmen adaylarının yazdıkları metinlerdeki verilenlerin, çarpma işlemine yönelik yazılan metinler dışında çoğunlukla açık bir şekilde ifade edildiği görülmektedir.
SINIF ÖĞRETMENİ ADAYLARININ DÖRT İŞLEM PROBLEMLERİNE YÖNELİK ÖYKÜLEYİCİ METİN YAZMA BECERİLERİNİN İNCELENMESİ
Keywords: Classroom Education; Sınıf Eğitimi